Features of clinical manifestations of gonarthritis in women with hypertension and overweight - I. M. Fushtey; A. M. Pidlubna (Сучасні медичні технології)
Abstract One of the diseases that is quite common in modern rheumatology and leads to dysfunction of the musculoskeletal system and creates a major medical and social problem, is gonarthrosis. The incidence of degenerative-dystrophic diseases in HA in women is two to four times higher than in men. In order to establish the patterns of clinical manifestations of GA in women with hypertension (GC) and overweight (HB) of the body, on the basis of the rheumatology department of the city KNP «City Hospital №10» ZMR (Zaporozhye), with informed consent, was prospectively examined 198 women for the period 2018–2020. According to the results of the study, a significant (p <0.05) deterioration of clinical symptoms in women with a combined course of HA with GC and HB, relative to the isolated course of HA, on the indicators: pain during active and passive movements and palpation, stiffness, crepitation and swelling of the joints. The correlations between clinical manifestations of HA, arthrosonographic data and BMI have been established. The characteristics of the pain syndrome associated with exercise, impaired mobility and functionality of the joints significantly increased with increasing stage of GA, joining comorbid pathology and increased BMI.